The Home Workplace A Builder's Guide to Its Environment, Energy and Economy. - Perley, Daniel R. (Cambridge Scholars Publisher, 2021)
The recent COVID-19-induced slamming of millions of information workers into the home workplace has made clear that the planning and management foundations for such a mass-migration are anything but solid. Now, the IT industry is scrambling to offer products which do not treat the (remote) worker as a third-class citizen.However, there is another problem, namely the lack of a coherent theory (and documented practice) about what wide-scale workplace decentralization will really do for the individual, the organization, the local community, and ultimately the planet. Indeed, the home workplace ca.